Comparison between two propagation methods in ‘Reina Claudia’ plum (Prunus domestica L.) - Vélez Sánchez, Javier E (2025)
[Objective] The propagation method of plum trees is crucial for production success, as it likely influences plant compatibility and performance. The objective of this research was to evaluate two propagation systems of the ‘Reina Claudia’ plum tree variety, comparing bud grafting and cuttings, to identify the method most compatible with the variety. [Methodology] Since 2018, an experiment has been conducted in Sesquilé, Cundinamarca, to compare the two propagation methods of ‘Reina Claudia’ plum trees (Prunus domestica L.). The experiment followed a completely randomized design. One method involved bud grafting onto a ‘common white’ peach rootstock (Prunus persica L.), while the other used cuttings from the same plum variety. [Results] Significant differences were observed in the main branch diameter, with trees propagated by cuttings (TPC) reaching 31.62 mm, compared to 17.74 mm in those propagated by grafting (TPG). Water potential in TPC trees ranged from 0 to -107.25 kPa, while in TPG trees, it ranged from 0 to -58.25 kPa. Stomatal conductance values were higher in TPG (0 to 879 mmol m-2 s-1) than in TPC (149.0 to 761.31 mmol m-2 s-1). The propagation method influenced both water potential and chlorophyll content in the plum trees. [Conclusions] The TPC trees exhibited greater vegetative growth, including increased height, leaf area, crown diameter, and crown volume. However, TPG trees demonstrated greater precocity.